Are CSF Pressure Factors Related to the Development of Post-dural Puncture Headache? - Kim, Seong Hoon; Kim, Tae Won; Shin, Hae Eun; Lee, Si Baek; Ryu, Dong Woo; Park, Jeong Wook (Frontiers in Neurology, 2019)
Post-dural puncture headache (PDPH) is an unfavorable situation seen in considerable number of patients even though atraumatic and small needle reduces its incidence. CSF pressures measured at the time of puncture change after CSF drainage. In the present study, we investigated relationships between CSF pressure-related factors and occurrence of PDPH. We prospectively enrolled 103 participants who underwent CSF studies for meningitis. Using a standardized protocol, CSF opening pressure (OP) and closing pressure (CP) were measured, and cerebrospinal elastance (ECS) and pressure-volume index (PVI) were investigated. Within 14 days after dural puncture, we confirmed PDPH. According to PDPH development, the CSF pressure factors and clinical variables were compared between PDPH and non-PDPH group. Of the 103 participants, 100 (97.0%) had decreased CP, 16 (15.5%) had values below 6 cmH2O and the pressure change after dural puncture (OP-CP) was 6.1 ± 3.1 cmH2O. PVI and ECS measured by CSF drainage were 99.8 ± 89.5 and 0.4 ± 0.2 cmH2O/mL. Among the demographic factors, body weight was correlated with OP (r = 0.27), CP (r = 0.35), and PVI (r = 0.20). Height was weakly correlated with CP (r = 0.199) During the study period, 22 participants (21.34%) developed PDPH. None of the CSF pressure factors were significantly different between the PDPH and non-PDPH group and did not contributed to the development of PDPH. CSF pressure factors might not be related to the development of PDPH.